Tin Nanoparticles Modified Electrode For Simultaneous Detection Of Cadmium (Cd) And Lead (Pb) Ions - Loo, Ji Yu (Universiti Sains Malaysia, 2022)
Heavy metal pollution in the environment has significantly endangered human health by accumulation of heavy metal ions within the food chain. Therefore, heavy metal detection is important for environmental monitoring. In this research, the tin nanoparticles (SnNPs) were synthesized using chemical reduction method and used for modification of Indium Tin Oxide (ITO) electrode for detection of heavy metal ions. The SnNPs were synthesized using two approaches, with and without the addition of polyvinylpyrrolidone (PVP), namely SnNPs WPVP, and SnNPs WOPVP, respectively. The as-synthesized SnNPs were drop casted on the ITO electrode with varying concentration, and with and without Nafion. The modified electrode was subjected to cyclic voltammetry (CV) and square wave anodic stripping voltammetry (SWASV). Nafion/SnNPs WPVP/ITO modified electrode showed good performance in simultaneous detection of Cd2+ and Pb2+ ions with linear range of 10-100 ppb, the limit of detections (LOD) for simultaneous detection of Cd2+ and Pb2+ ions were 1.44 ppb and 1.97 ppb, respectively. The sensitivity of the Nafion/SnNPs WPVP/ITO modified electrode was 0.25 μA/ppb and 0.20 μA/ppb towards Cd2+ and Pb2+ ions, respectively. The modified electrode showed high selectivity towards detection of Cd2+ and Pb2+ ions in interference study. The feasibility of the modified electrode was studied in real seawater sample for detection of Cd2+ and Pb2+ ions and successfully detected the presence of Pb2+ ions in the seawater sample. Thus, the results revealed that the SnNPs/ITO electrode can be used as heavy metal ions sensor.